Efficiency of aeration system in wastewater treatment plants - Kumar, Sri Ruthira (2007)
The most important factor in selecting aeration equipment for a specific application is the oxygen transfer rate. Other factors that are equally important are reliability, serviceability, capital cost, system appurtenances and cost of operation and maintenance. Although there are many systems designed to aerate and mix the waste water, they vary in their effectiveness in providing uniform oxygen dispersion. It is the intention of the study to evaluate the performance of different types of aeration devices based on dissolved oxygen (DO) readings and costing. To achieve this objective, experimental work were carried out on five different aeration devices namely brush aerator, tornado, surface aerator, aspirator and diffusers on five different sewerage treatment plant with average PE of 2000. Through the experiment it was found that aspirator was able to achieve 1 to 2 mg/l dissolved level while meeting the regulators requirement on biochemical oxygen demand level. In the terms of electricity, aspirator needed the lowest consumption compared to the other type of device system. A detailed study on costing was done for the last 6 months in term of operating and maintenance on the aeration device and was found that aspirator was the cheapest to maintain compared to the others. While meeting the biochemical oxygen demand standard as require by the regulators, this outcome of the study would be a crucial factor when selecting a suitable aeration device in sewerage industry in future.